Strategies of the Investment and One-Stop Integrated Service Office in Increasing Investment in Jember Regency - Lailatul Munawaroh Laila; Asmuni (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Economic growth in a region is influenced by investment. So that the existence of business actors either on a macro or micro scale contributes to subsequent economic growth. Therefore, the government must be responsible for the investment process so that all parts of society benefit from investment. This research argues that an adequate licensing system is interesting to study. This is because an adequate licensing system has a huge impact. For example, investment growth can increase the amount of goods or services sold, create added value, increase labor, and other economic resources. One of the objectives of this research is to find the strategies used by the efforts of the One-Stop Investment and Integrated Services Agency (DPMPTSP) in increasing investment in Jember Regency. In addition, this study also wanted to find out the factors that support and hinder the efforts of the One-Stop Investment and Integrated Services Office to increase investment in Jember Regency. The results of this study state that the Jember Regency government has created an investment strategy and improved the quality and skills of the community through training. Investors and businesses will better understand their responsibilities to report investment activities and conduct complete investment promotion activities. An additional strategy proposed by the DPMPTS of Jember Regency is local regulations relating to the investment sector. This research uses Brayson's theory explaining that strategic planning is conducted using five indicators: establishing the vision, mission and goals of the organization; conducting an analysis of the internal and external environment; finding strategic issues; and then creating a strategy. The conclusion shows that of the five measurement criteria four of them run satisfactorily. While one of them is not good, namely the strategy developed by DPMPTSP Jember Regency is less than optimal as in the case of the absence of local regulations that can support future investment, the absence of a potential map and opportunity map, as well as limited internal and external human resources.